2014
DOI: 10.1007/s10616-013-9569-z
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord-derived mesenchymal stem cells differentiate into epidermal-like cells using a novel co-culture technique

Abstract: Human umbilical cord-derived mesenchymal stem cells (hUCMSCs) isolated from human umbilical Wharton's Jelly are a population of primitive and pluripotent cells. In specific conditions, hUCMSCs can differentiate into various cells, including adipocytes, osteoblasts, chondrocytes, neurocytes, and endothelial cells. However, few studies have assessed their differentiation into epidermal cells in vitro. To assess the potential of hUCMSCs to differentiate into epidermal cells, a microporous membrane-based indirect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
(33 reference statements)
0
16
0
Order By: Relevance
“…Unlike macrophages, which express multiple surface receptors, MSCs are derived from the mesoderm and do not differentiate into hematopoietic cells. However, they are multipotent, with an ability differentiate into adipocytes, neuronal cells and osteoclasts 59 . Fewer receptors are therefore known on MSCs, although, because of the propensity of these cells to differentiate into adipocytes, they have been found to express SRs and endocytose lipids 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Unlike macrophages, which express multiple surface receptors, MSCs are derived from the mesoderm and do not differentiate into hematopoietic cells. However, they are multipotent, with an ability differentiate into adipocytes, neuronal cells and osteoclasts 59 . Fewer receptors are therefore known on MSCs, although, because of the propensity of these cells to differentiate into adipocytes, they have been found to express SRs and endocytose lipids 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings of both experimental studies and clinical trials demonstrated that MSCs were able to repair skin. First, MSCs can differentiate into epidermal-like cells [28] and enhance the reepithelialization during wound repair. Animal autografting experiments with MSCs showed the increased number of epidermal ridges and thickness of the regenerated epidermis [29].…”
Section: Possibility Of Mscs In Regeneration Of Sweat Glandsmentioning
confidence: 99%
“…Certain characteristics make MSCs attractive as therapeutic candidates, including innate pluripotency, the capacity to facilitate the repair of lesions through multiple avenues in immune regulation, angiogenesis and neurogenesis, and their immune privileged status (9). MSCs may be isolated from various sources, including bone marrow, adipose tissue (10), umbilical cord (11) and peripheral blood, among which the major and most frequently studied source is the bone marrow. Furthermore, a growing body of pre-clinical studies has consistently demonstrated that bone marrow-derived MSCs (BM-MSCs) are capable of safely ameliorating clinical outcomes of certain neurological degenerative diseases, including stroke (12) and multiple sclerosis (13,14).…”
Section: Introductionmentioning
confidence: 99%